Kepatuhan Konsumsi Tablet Fe, Lama Menstruasi, Perilaku Makan dengan Kejadian Anemia pada Remaja Putri SMKN 4 Kota Mataram - Zaidah, Una; Ningsih, Murtiana; Ali, Nur Aini Abdurrahman (LPPM Institut Pendidikan Nusantara Global, 2024)
As many as 32% of teenage girls in Indonesia suffer from anemia caused by iron deficiency. This study aims to identify adherence to Fe tablet consumption, length of menstruation, eating behavior, and the incidence of anemia in adolescent girls, as well as to analyze the relationship between adherence to Fe tablet consumption, length of menstruation, eating behavior and the incidence of anemia in adolescent girls at SMKN 4 Mataram City. The research method is to use a quantitative approach with a cross sectional design. The population in this study were all young women at SMKN 4 Mataram City with a total of 760 people, and a total sample of 88 people. Data analysis uses univariate and bivariate analysis. The research results showed that as many as 98.9% (87) of young women did not comply with taking Fe tablets, 44.3% of young women experienced menstruation for more than seven days, and only 18.2% of young women had good eating behavior. Of the total sample, 20.5% of young women experienced anemia. Bivariate test results showed that there was no relationship between adherence to consuming Fe tablets and the incidence of anemia (P=0.610), there was no relationship between the length of menstruation and the incidence of anemia (P=0.108), and there was no relationship between eating behavior and the incidence of anemia in adolescent girls. at SMKN 4 Mataram city (P=0.318).